How similar is the electronic structures of β-lactam and alanine?. (February 2016) - Chatterjee, Subhojyoti; Ahmed, Marawan; Wang, Feng
Abstract: The C1s spectra of β-lactam i.e. 2-azetidinone (C3 H5 NO), a drug andl -alanine (C3 H7 NO2 ), an amino acid, exhibit striking similarities, which may be responsible for the competition between 2-azetidinone and the alanyl-alanine moiety in biochemistry. The present study is to reveal the degree of similarities and differences between their electronic structures of the two model molecular pairs. It is found that the similarities in C1s and inner valence binding energy spectra are due to their bonding connections but other properties such as ring structure (in 2-azetidinone) and chiral carbon (alanine) can be very different. Further, the inner valence region of ionization potential greater than 18 eV for 2-azetidinone and alanine is also significantly similar. Finally the strained lactam ring exhibits more chemical reactivity measured at all non-hydrogen atoms by Fukui functions with respect to alanine. Highlights: Reveal insight why 2-azetidinone and alanine molecules compete in binding proteins. Electronic structures of 2-azetidinone and alanine are studied by DFT studies. Responsible similarities of the pair are C1s XPS, γ-ray profiles and Doppler shift.